PENINGKATAN MINAT SISWA DAN KEMAMPUAN MEMAHAMI GEOGRAFI REGIONAL MELALUI MODEL PEMBELAJARAN PENEMUAN DENGAN STRATEGI MEMBACA DAN MELENGKAPI PETA DASAR - Sutrisno Sutrisno (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2017)
This classroom action research aims at improving: (1) the students’ competence of understanding regional geography subject, and (2) student interest in learning regional geography subject through discovery learning model with reading and completing basic map strategy. The research procedure consists of three cycles. Each cycle includes four phases; they are planning, implementation, observation, and reflection. The research subject is students of IXB class. This class is selected because it lacks interest and competence in understanding regional geography learning compared to other classes. The result of the action research shows that the implementation of learning model with reading and completing basic map strategy can improve the interest and understanding competence of regional geography.